A STUDY ON KNOWLEDGE, ATTITUDE AND PRACTICES TOWARDS HEPATITIS B VACCINATION AMONG PATIENTS RECEIVING MEDICAL SERVICES AT KASANGATI HEALTH CENTRE IV, WAKISO DISTRICT. A CROSS-SECTIONAL STUDY . - Maganyi , Ethel (Student’s Journal of Health Research Africa, 2023)
Background: Hepatitis B Virus infection is a fatal hepatocellular infection that is caused by Hepatitis B virus in the low resource settings like Uganda with a prevalence of 4.3%, Hepatitis B virus infection. Vaccination services have been recommended by the ministry of health to all individuals. Purpose: The purpose was to determine the knowledge , Attitude and Practices towards hepatitis B vaccination among patients receiving medical services at Kasangati health centre IV . Objectives: The objectives of the study were to determine the knowledge, attitude and practice towards Hepatitis B vaccination among patients receiving medical services at Kasangati Health Centre IV. Methodology: The study was cross-sectional involving 100 patients at Kasangati Health Centre IV. Simple random sampling was used and information was collected by the researcher using the semi-structured questionnaires that sought information on respondents` social demographic data, knowledge, attitude and practice towards Hepatitis B vaccination. Data was analyzed using Microsoft word and excel. Results : The study findings showed that 61% of the respondents had poor knowledge about the number of doses of a complete full dose vaccination , while 39% had good knowledge . Majority of the respondents had poor knowledge about the number of doses necessary for complete hepatitis B vaccination . Conclusion: The study found out that majority of the respondents had an average knowledge about Hepatitis B vaccination Therefore this finding clearly shows the risk of Hepatitis B infection of the respondents at Kasangati Health Centre IV in Wakiso District due to average knowledge. Recommendation: The ministry of health through Kasangati Health Centre IV should conduct health education campaigns about Hepatitis B vaccination among the people to as to improve their knowledge, attitude and practice towards Hepatitis B vaccination.